ANALISIS PERTUMBUHAN EKONOMI DI INDONESIA TAHUN 2006-2020 - Herbowo, Herbowo; Cahyo, Heru; Purnomo, Sodik Dwi (STKIP Persada Khatulistiwa Sintang, 2023)
Economic growth is an indicator of successful development achieved and can be used to determine further development policies. This study aims to analyze the effect of oil prices, imports, exports, interest rates, inflation, and the money supply on economic growth in Indonesia in 2006 to 2020. This study uses a quantitative approach with research data sourced from the Indonesian Central Bureau of Statistics and Bank Indonesia. The research method is multiple linear regression. The results show that oil prices, exports, and interest rates have a positive and significant effect on economic growth in Indonesia. Meanwhile, imports, inflation and the money supply have a negative and significant effect on economic growth in Indonesia. The implication of this research is that the government must reduce dependence on imports of raw materials and food by facilitating alternative raw materials and food that can be developed independently. In addition, the government must control the amount of money in circulation according to the capacity of the community's economy